Rationale of students' failure in comprehending theoretical computer science courses - Qureshi, M.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
Being a good IT solution provider one require good programming background. For a good programmer one need to have a solid back ground of algorithms i.e. Theoretical aspects of the computer science. Most of the students of computer science do not understand the importance and do not give proper attention to Theoretical Computer Science (TCS) courses. As a result perform bad in these specialized courses. Intention of this research is to find the reasons of students' failure in grasping the subject matter in the light of the feedback of currently studying students as well as well experienced teachers and professionals. The study resulted in a set of suggestions including the usage of better simulation tools, better environment, visualization, etc. Â© 2014 IEEE.